The four feathers - Mason, A. E. W. 1865-1948; Rózsa, Miklós 1907-1995 (<<The>> Criterion collection, 2011)
"Ein wegen Austritts aus der Armee auch von seiner Braut wegen Feigheit gedemütigter britischer Offizier vollbringt während des Mahdi-Aufstands im Sudan (1898) größere Mutbeweise als seine Verächter. Aufwendig inszenierter Abenteuerfilm mit publikumswirksamen Massenszenen im Schlachtgetümmel. [...]" [filmdienst.de]
Original: Großbritannien 1939
DVD special edition features: new high-definition digital restauration ; audio commentary by film historican Charles Drazin ; new video interview with David Korda, son of director Zoltán Korda ; "A day at Denham" a short film from 1939 featuring footage of Zoltán Korda on the set of "The four feathers" ; theatrical trailer ; plus: an essay by film critic Michael Sragow
Bildformat 1.37:1
Keywords: Film; DVD-Video